Karakteristik Asas Kebebasan Berkontrak dalam Perjanjian Berbasis Syariah - Muhammad Sjaiful (Faculty of Law Hang Tuah University, 2015)
Sharia-based contract is an agreement that is derived from the nomenclature of Islamic law. It is definitely designed as the agreement that shall refer to norms based on legal sources of Islam, i.e. the Qur'an and the Hadith of the Prophet Muhammad. This paper discusses the main issue as follows: the dynamics of developments and characteristic principle of freedom of contract in Sharia-Based Agreement